Waardenburg syndrome type I. - Pawar, M.K.; Yethenpa, S.O. (European Journal of Pediatric Dermatology, 2016)
Waardenburg syndrome type I (WSI) is a rare, autosomal dominant genetic disorder characterized by pigmentary disturbances of the iris, skin, hair, stria vascularis of the cochlea along with dystopia canthorum, sensorineural hearing loss and reduced vision in some cases. Here, we report a case of an 8-year-old boy with abnormal pigmentation of the hair and iris along with dystopia canthorum, later diagnosed to have WSI.